Typology of agricultural holdings: a starting point for understanding the performance of irrigated systems in Baalbek Al Hermel Lebanon. - Al fakih, Ahmad; Darwich, Salem; Madau, Fabio (Technium Sustainability, 2024)
The Mediterranean region is one of the most vulnerable regions to climate change (CC) which raises important problems for Mediterranean agriculture. In fact, climate disruption creates some uncertainty in the decision-making of farmers in the management of their farms. This understanding can help researchers to better orient agricultural research on adaptation at the farm level and can help policy makers to develop adaptation policies. The semi-arid region of Baalbeck El Hermel is increasingly threatened by climate change. The agricultural systems constituting the main source of household subsistence in this zone show a significant vulnerability to these disturbances, especially about the limit in water resources. In this research we propose a framework to represent agricultural activities using typologies of farms and production units aggregated at a regional scale. We used empirical data from a local case study of the five most representative farming systems in the Baalbek-Hermel Governorate. Analysis of the results showed several behaviors and several levels of resilience of these farms:1-farms specializing in market gardening or perennial crops are very sensitive to drought conditions and are not resilient in the face of water limit conditions;2-the diversified farm with olive tree dominance is less sensitive and more resilient.